The Inflammatory Response to Ventricular Assist Devices - Radley, Gemma; Pieper, Ina Laura; Ali, Sabrina; Bhatti, Farah; Thornton, Catherine A. (Frontiers in Immunology, 2018)
The therapeutic use of ventricular assist devices (VADs) for end-stage heart failure (HF) patients who are ineligible for transplant has increased steadily in the last decade. In parallel, improvements in VAD design have reduced device size, cost, and device-related complications. These complications include infection and thrombosis which share underpinning contribution from the inflammatory response and remain common risks from VAD implantation. An added and underappreciated difficulty in designing a VAD that supports heart function and aids the repair of damaged myocardium is that different types of HF are accompanied by different inflammatory profiles that can affect the response to the implanted device. Circulating inflammatory markers and changes in leukocyte phenotypes receive much attention as biomarkers for mortality and disease progression. However, they are seldom used to monitor progress during and outcomes from VAD therapy or during the design phase for new devices. Even the partial reversal of heart damage associated with heart failure is a desirable outcome from VAD use. Therefore, improved understanding of the interplay between VADs and the recipient’s inflammatory response would potentially increase their uptake, improve patient lives, and fuel research related to other blood-contacting medical devices. Here we provide a review of what is currently known about inflammation in heart failure and how this inflammatory profile is altered in heart failure patients receiving VAD therapy.